PERANCANGAN APLIKASI AUGMENTED REALITY UNTUK EDUKASI PENERAPAN KONSEP GREEN ECONOMY DALAM PENGEMBANGAN DESA WISATA SEBAGAI UPAYA MEWUJUDKAN PEMBANGUNAN BERWAWASAN LINGKUNGAN - Victor Marudut Mulia Siregar; Mhd Ali Hanafiah (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
This study aims to build an augmented reality application that can be used as a means of educating the application of the green economy concept in the development of tourist villages. The use of augmented reality technology is used to overcome the lack of public understanding of the concept of a sustainable green economy and the lack of education about the importance of protecting the environment for environmental sustainability. This research has an important urgency to be carried out as an effort to realize environmentally sound development in the development of tourist villages. The results of this study are Augmented Reality applications that can be used as educational media for the community to apply the green economy concept in the development of tourist villages as an effort to realize environmentally sound and environmentally friendly development with the green economy concept. Through this application, people's understanding of the importance of environmental sustainability in the development of tourist villages increases. With this application, the development of an environmentally sound and environmentally friendly tourist village in the Nagori Tigaras Tourism Village, Simalungun Regency can be achieved better.